Vol. 3, No. 1, September 2021 - Iip Nurhidayah (Scientia Regendi, 2021)
This study aimed to describe the influence of leadership and organizational culture on employee job satisfaction at the Sukatani Public Health Center, Purwakarta Regency, both individually and together. This research was conducted at the Sukatani District Health Center. The research method used is a survey method. Research respondents were employees of Sukatani Public Health Center, Purwakarta Regency, 40 people were selected based on the proportional stratistified random sampling technique. The instrument used is a questionnaire to collect data on the variables of leadership, organizational culture and employee job satisfaction. Data analysis used simple correlation technique, multiple correlation, and regression technique consisting of simple and multiple linear regression. Previously, the data analysis requirements were tested, namely normality test and homogeneity test. The results of this study found that: first, there is a positive influence between leadership on employee job satisfaction at the Sukatani Health Center, Purwakarta Regency. This means that the better the leadership of an employee, the higher the employee's job satisfaction. Second, there is a positive influence of organizational culture on job satisfaction of Sukatani Public Health Center employees, Purwakarta Regency. This means that the better the organizational culture in which an employee works, the higher the employee's job satisfaction. Third, there is a positive influence of leadership and organizational culture together with job satisfaction of Sukatani Public Health Center employees, Purwakarta Regency. Thus, it means that the better the superior's leadership on an employee and the better the organizational culture in which he works, the higher the employee's job satisfaction.